Comparison of Degradation Behaviour of the Painting Paper in Japanese Scrolls for Moist Heat and Sealed Tube Ageing Methods. (3rd October 2022) - Lee, Kang; Enomae, Toshiharu; Inaba, Masamitsu
ABSTRACT : One of the factors affecting the life expectancy of hanging scrolls is the storage environment. Our study focused on clarifying the degradation behaviour of painting paper, concentrating on the specific storage conditions that provide an airtight environment in a storage box and the stacked structure of the rolled paper rather than considering the materials of the wooden storage box or the gases generated from it. The degradation behaviour and rates for the sealed tube and moist heat ageing methods, excluding the additional effects of light and air pollutants, were compared. When the painting paper was immersed in a CuSO4 ・5H2 O solution instead of a copper green pigment, the oxidation of the painting paper, attributed to Cu 2+, proceeded faster with the sealed tube method than with the moist heat method. The co-occurring organic acids generated, namely glycolic and formic acids, which were secondary components, were detected in a higher amount in the first lining paper than the painting paper. This implies that the acids migrated from the painting paper into the lining paper. However, oxalic acid, which was the main component, did not significantly migrate and remained in the reaction system in the sealed tube without volatilising. This increased the hydrogen ion concentration in the painting paper and accelerated acid hydrolysis. Consequently, discolouration and a decrease in the degree of polymerisation and physical strength proceeded faster with the sealed tube method than with the moist heat method. Thus, although this result does not necessarily invalidate the storage system of a rolled hanging scroll in a box, the storage of a deteriorated hanging scroll in a closed system is expected to degrade the painting paper faster than it would in an open system.